COVID-19 geopolitics: silence and erasure in Cambodia and Myanmar in times of pandemic. Issue 4 (2nd September 2020) - Grundy-Warr, Carl; Lin, Shaun
ABSTRACT: COVID-19 has become a global public health pandemic which requires scientific, technical, public policy and health system responses at multi-scales. COVID-19 is also a pandemic that is impacting socio-economic and political systems in profound ways. This paper briefly outlines why and how pandemics may expose uneven socio-economic geographies of vulnerability and risk, and also be thought of in relation to environmental and non-human challenges to our geopolitical map of territorial nation-states and sovereignties. In relation to Southeast Asia we argue that preexisting and ongoing political-economy linkages are shaping key responses to COVID-19. In particular, we consider the geopolitical and geoeconomic reasoning of Cambodia and Myanmar, and their relations with China. We reflect on the factors that shape their national responses in response to the pandemic, characterized by certain silences and erasures to their local geographies.